A Logical Calculus of Meaning and Synonymy. - Moschovakis, Yiannis N. (Linguistics & Philosophy, 2006)
The article talks about the logical calculus of meaning and synonymy. Richard Montague developed formal semantics for natural language. The applications to fragments of natural language were formalized or translated into Formal language of recursion (FLR). The development of the theory of referential intentions for the formal language is discussed.